Organic extracts from Indigofera suffruticosa leaves have antimicrobial and synergic actions with erythromycin against Staphylococcus aureus - Bezerra dos Santos, Ana Thereza; Araújo, Tiago Ferreira da Silva; Nascimento da Silva, Luis Cláudio; Silva, Cleideana Bezerra da; Oliveira, Antonio Fernando Morais de; Araújo, Janete Magali; Correia, Maria Tereza dos Santos; Lima, Vera Lúcia de Menezes (Frontiers in Microbiology, 2015)
A characteristic feature of Staphylococcus aureus is its ability to acquire resistance to antimicrobial agents. There is a need, therefore, for new approaches to combat this pathogen; for example, employing a combination of plant-derived products and antibiotics to overcome bacterial resistance. Indigofera suffruticosa is a plant popularly used to treat infections and has verified antimicrobial action. Here, we investigate the antimicrobial activity of different extracts from I. suffruticosa against S. aureus and their synergistic effects with erythromycin. Leaves of I. suffruticosa were extracted sequentially using diethyl ether, chloroform and acetone and the antimicrobial activity of each extract then tested against nine clinical isolates of S. aureus. Minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were determined by microdilution tests, while the fractional inhibitory concentration (FIC) was assessed by checkerboard assay. All organic solvent extracts showed antimicrobial activity against S. aureus strains. The acetone extract was the most potent inhibitor of S. aureus (MIC and MBC of 0.78 and 3.12 mg/mL), followed by the chloroform extract (MIC and MBC of 3.12 and 6.25 mg/mL). Furthermore, acetone or chloroform extracts of I. suffruticosa enhanced the activity of erythromycin against S. aureus (FIC ≤ 0.5). We conclude that organic extracts from leaves of I. suffruticosa, alone or combined with erythromycin, are promising natural products for the development of new anti-S. aureus formulations.